Religious Change and Secularisation in Scotland: An Analysis of Affiliation and Attendance. Issue 2 (May 2017) - Clements, Ben
Abstract : Building onBrown (1997) and Field's (2001) research into religious decline and secularisation in Scotland in the later decades of the 20 th -century, this article uses data from recurrent social surveys, nationally-representative of the Scottish adult population, to assess the nature and extent of religious change in the 21 st -century. It examines recent trends in religious affiliation and attendance in Scotland, compares key indicators in England and Scotland to assess areas of similarity and difference in terms of religion and secularity, and assesses the contemporary socio-demographic basis of affiliation and attendance in Scotland. The empirical results show that religious affiliation and attendance have further attenuated in Scotland in recent years, with a growing proportion of adults reporting that they were raised outside of any religious tradition. Indicators of secularity are most marked amongst younger age groups. The 'haemorrhage of faith' documented in the latter part of the 20 th- century in Scotland has continued into the early part of the 21 st -century.